The Invasive Plants Species along the Hiking Track of Mount Panderman Nature Tourism, Batu, East Java - Septiadi, Luhur; Wahyudi, Didik; Rachman, Rhesma Sylvia; Syafrudin, Syafrudin; Alfaruqi, Nuri Thobibatus Shofia (Graduate School, Universitas Brawijaya, 2018)
Indonesia has the highest biodiversity that places ecotourism as a sustainable development sector. The negative impact of ecotourism is the vulnerability to invasive plant species growth. They invade the habitat of the native plants and potentially alter the biodiversity balance. This invasive plant introduction is predicted caused by tourist and hiker visits. Therefore, the inventory of invasive plant species is urgently needed. The field survey was conducted on March 11-12, 2017 to inventory invasive plant species along the Panderman Mountain hiking track that common travelers explored and then identified. Species of Pinus Caribaea, Chromolaena odorata, Lantana camara, Leucaena leucocephala, Pennisetum purpureum are categorized invasive plants. Four species of plants otherwise potentially invasive include Calliandra calothrysus, Ageratum conyzoides, Bidens pilosa, and Acacia deccurens. The widespread access to protected environmental destinations leads to the spread of highly invasive species. The impact of invasive species depends on factors such as reproduction rate, vegetative phase, adaptability of seeds that can withstand adverse conditions and in particular human vectors as a way of spreading them.Keywords: Batu, Ecotourism, Hiking track, Invasive plants, Panderman Mountain.